Amendment of organic compost proprieties through composting-vermicomposting integration - Maronezi, Vanessa (2021)
The aim of the current study is to evaluate the effects of integrating composting-vermicomposting to improve the organic compost as from the physicochemical analyses and by their application on Brachiaria decumbens growth. Experiments carried out in composting unit used 30:1 ratio of nitrogen-rich organic waste (raw vegetables, fruits and cooked food) and carbon (dry grass) in 2 pile configurations (with, or without passive aeration). After 60 days, product was subjected to vermicomposting for 45 days. Composts were analyzed to check their quality (temperature, pH, moisture, organic carbon, nitrogen and phosphorus levels), as well as compared to each other as biofertilizers (10% (w/v)) for B. decumbens growth. Data have suggested that the vermicomposting process improved the compost pile by increasing its nitrogen (1.26% to 1.95%), phosphorus (0.64% to 1.2%) and organic carbon contents (17.1% to 18.9%). B. decumbens growth showed no significant differences between those treatments, which indicates that organic fraction should be increased (>10%) to release their nutrients to plant.